Pathogenomic analysis and characterization of Pasteurella multocida strains recovered from human infections - Thomas R. Smallman; Laura Perlaza-Jiménez; Xiaochu Wang; Tony M. Korman; Despina Kotsanas; Justine S. Gibson; Conny Turni; Marina Harper; John D. Boyce (Microbiology Spectrum, 2024)
ABSTRACTPasteurella multocida is an upper respiratory tract commensal in several mammal and bird species but can also cause severe disease in humans and in production animals such as poultry, cattle, and pigs. In this study, we performed whole-genome sequencing of P. multocida isolates recovered from a range of human infections, from the mouths of cats, and from wounds on dogs. Together with publicly available P. multocida genome sequences, we performed phylogenetic and comparative genomic analyses. While isolates from cats and dogs were spread across the phylogenetic tree, human infections were caused almost exclusively by subsp. septica strains. Most of the human isolates were capsule type A and LPS type L1 and L3; however, some strains lacked a capsule biosynthesis locus, and some strains contained a novel LPS outer-core locus, distinct from the eight LPS loci that can currently be identified using an LPS multiplex PCR. In addition, the P. multocida strains isolated from human infections contained novel mobile genetic elements. We compiled a curated database of known P. multocida virulence factor and antibiotic resistance genes (PastyVRDB) allowing for detailed characterization of isolates. The majority of human P. multocida isolates encoded a reduced range of iron receptors and contained only one filamentous hemagglutinin gene. Finally, gene-trait analysis identified a putative L-fucose uptake and utilization pathway that was over-represented in subsp. septica strains and may represent a novel host predilection mechanism in this subspecies. Together, these analyses have identified pathogenic mechanisms likely important for P. multocida zoonotic infections.IMPORTANCEPasteurella multocida can cause serious infections in humans, including skin and wound infections, pneumonia, peritonitis, meningitis, and bacteraemia. Cats and dogs are known vectors of human pasteurellosis, transmitting P. multocida via bite wounds or contact with animal saliva. The mechanisms that underpin P. multocida human predilection and pathogenesis are poorly understood. With increasing identification of antibiotic-resistant P. multocida strains, understanding these mechanisms is vital for developing novel treatments and control strategies to combat P. multocida human infection. Here, we show that a narrow range of P. multocida strains cause disease in humans, while cats and dogs, common vectors for zoonotic infections, can harbor a wide range of P. multocida strains. We also present a curated P. multocida-specific database, allowing quick and detailed characterization of newly sequenced P. multocida isolates.